Analisis Pengaruh Electronic Word of Mouth Instagram terhadap Minat Pembelian dengan Studi Kasus pada Restoran Mie Akhirat Cabang Darmo Surabaya - Ahmad, Ifan; Novaria, Rachmawati; Maruta, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2017)
This study entitled "Analysis of Effect of Electronic Word of Mouth Instragram to Purchase Interest in the Case Study in Mie Restaurant Hereafter Branch Darmo Surabaya". This study aims to find out is there any influence of Electronic Word of Mouth Instragram the interest in the purchase and the truth of the indicator variable economic incentive Electronic Word of Mouth dominant influence on consumer pembellian interest. The population in this study is the consumer direct outlet Citarum Mie Hereafter Jln 2, Darmo, Wonokromo, Surabaya encountered during a predetermined period.          Electronic variable used is the word of mouth that consists of concern for others, expressing positive feelings, helping the company, and economic incentives as the independent variable and Interest Purchase as the dependent variable.         In conclusion, as follows: (1) Partially concern for others is not positive and significant effect on the interest shown by the value of the purchase of t = - 0.0385. and sig. 0.701 (2) Partially expressing positive feelings are not positive and significant effect on the interest shown by the value belli t = -0.025, and sig. 0.980, (3) Partially helping the company, positive and significant impact on the buying interest is indicated by the value t = 2.476. and sig. 0.015, (4) Partially economic incentives and significant positive effect on the buying interest is indicated by the value t = 3.508 and sig. 0,001 (5) economic incentives dominant influence on buying interest and value adjusted R2 of 0.384. This means a 38.4% interest in buying explained by concern for others, expressing positive feelings, helping the company, and economic incentives, while 61.6% is explained by other variables not examined in this study.  Keywords: Electronic word of, concern for others, expressing positive feelings, helping the company, and the economic incentive, interest in purchasing